2005
DOI: 10.1111/j.1365-2141.2005.05618.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonal granulocytes in polycythaemia vera and essential thrombocythaemia have shortened telomeres

Abstract: The purpose of this study was to evaluate telomere length in peripheral blood granulocytes and mononuclear cells collected from 22 women with polycythaemia vera (PV) and essential thrombocythaemia (ET). PV and ET are chronic myeloproliferative diseases whose heterogeneity of stem cell origin and clonal development has been established through analysis of X-chromosome inactivation patterns. The results from clonality assay and determination of telomere length show that only clonal granulocytes have shortened te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…By taking advantage of random inactivation of X-chromosome-linked polymorphisms, clonality has been studied in CMPDs, initially by Fialkow and coworkers, [144][145][146][147] and later by other groups using different polymorphisms. [148][149][150] Interestingly, it seems as if clonality in CMPD is also linked to both shortened telomeres 151,152 as well as to significantly increased levels of telomerase activity 153 as opposed to nonclonal CMPD and normal bone marrow cells. Moreover, similar to what has been described in CML, 138 telomere length seems to be significantly reduced in (presumably clonal) myeloid cells as opposed to (non-clonal) T-lymphocytes.…”
mentioning
confidence: 99%
“…By taking advantage of random inactivation of X-chromosome-linked polymorphisms, clonality has been studied in CMPDs, initially by Fialkow and coworkers, [144][145][146][147] and later by other groups using different polymorphisms. [148][149][150] Interestingly, it seems as if clonality in CMPD is also linked to both shortened telomeres 151,152 as well as to significantly increased levels of telomerase activity 153 as opposed to nonclonal CMPD and normal bone marrow cells. Moreover, similar to what has been described in CML, 138 telomere length seems to be significantly reduced in (presumably clonal) myeloid cells as opposed to (non-clonal) T-lymphocytes.…”
mentioning
confidence: 99%
“…Genomic DNA was isolated from PMN and MNC using a DNA purification kit (Amersham, Little Chalfont, UK). TRF were evaluated with a chemiluminescent assay kit (Telo-TAGGG telomere length assay, Roche, Mannheim, Germany) as described before [10]. Complete engraftment was obtained in all cases and full donor chimerism confirmed by short tandem repeat analysis on peripheral blood and bone marrow samples obtained periodically after HSCT.…”
mentioning
confidence: 99%
“…Although previous work has demonstrated reductions in TL in small numbers of patients with PV and ET, 17 one of the limitations of previous studies of TL in MPN has been the inability to account for the mixed chimerism between mutated and nonmutated cells, which varies among MPN patients. However, with the advent of quantitative assays for JAK2 617F mutational burden and for X-chromosome inactivation, we are able to assess the relationship between the size of the MPN clone and TL.…”
Section: Discussionmentioning
confidence: 96%
“…17 In this study, we analyzed a large cohort of MPN patients to further characterize variations of TL in relation to age, gender, clonality and JAK2 V617F allelic burden. We showed that, similar to normal individuals, MPN patients exhibit decreased TL with age, and that there was shorter TL in males than females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation